Physical Geographical Factors Leading to the Disparity of Regional Development: The Case Study of Java Island - Rista Ardy Priatama; Ernan Rustiadi; Widiatmaka Widiatmaka; Andrea Emma Pravitasari (Faculty of Geography, Universitas Gadjah Mada, 2022)
The complexity of regional disparity has encouraged viewing this issue from various perspectives, one of which is the role of physical geography in disparity. On Java Island, an observation on the role of geographical aspect is needed due to the spatial sturdiness of disparity. This study aims to provide quantitative proof that differences in the physical geography of Java’s regions account for the persistent regional disparity. We applied two approaches namely correlation and typology, employing data of physical geographical attributes and development level. The methods used were correlation analysis, factor analysis, cluster analysis, and one-way ANOVA. Based on the correlation approach, we found the association of regional development level with terrain ruggedness, soil parent materials, sea depth, elevation, and precipitation. Then, based on endowment-based typology approach, Java’s regions could be grouped into lowland, volcanic, old volcanic, and calcareous dry regions. The two latter performed poorly in all socio-economic indicators examined.